School supervision and the evaluation of educational quality within the framework of Sustainable Development Goal 4 of the 2030 Agenda: challenges and proposals - Valdez Miramontes, José Augusto (2025)
The document presents the results of a literature review on the current demands faced by citizens in a globalized world and their connection to the 2030 Agenda for Sustainable Development of the United Nations. In particular, it analyzes the role of school supervision in Mexico as a key element for implementing and evaluating educational policies that promote quality, inclusive, and equitable education, as established in Sustainable Development Goal 4. School supervision is explored through its functions of advising, pedagogical support, control, and administration, which aim to align educational processes with quality models and respond to the needs of the educational community.To face the challenges of educational modernization and globalization, the document proposes the creation of a community of practice for telesecundaria school supervisors. This collaborative space would allow for the exchange of experiences and the development of competencies that have so far been insufficiently addressed in continuous training, facilitating a more professionalized and effective supervision. Furthermore, the community of practice seeks to establish a support network among supervisors to strengthen educational management through collaborative strategies, aligning the Mexican educational system with international commitments and responding to the current demands of educational systems.